WORK READINESS REVIEWED FROM LEARNING ACHIEVEMENT OF COMPUTER ACCOUNTING SUBJECT, CAREER GUIDANCE, AND WORK MOTIVATION OF CLASS XII STUDENTS ACCOUNTING SKILL PROGRAM OF SMK NEGERI 1 SUBOH SITUBONDO - Wiwin Kusbiyantari; Hari Sukarno; Yuniorita Indah Handayani (STIE Mandala Jember, 2019)
The purposes of this study are: 1) To analyze the influence of learning achievement of computer accounting subject, career guidance and work motivation partially to the work readiness. 2) To study the influence of learning achievement computer accounting subject, career guidance and work motivation simultaneously to the work readiness. The samples in this study were the students of class XII Accounting skill program of SMK Negeri 1 Suboh Situbondo which amounted to 55 people. This research includes the type of explanatory research. Independent variables of this study are learning achievement of computer accounting subject (PB), career guidance (BK) and work motivation (MK) while dependent variable is work readiness (KK). Data analysis used is test of validity and reliability, multiple linear regression analysis, classical assumption test and hypothesis test. Regression analysis results obtained equation of regression line. This can be seen from the linear regression equation as follows KK = 20,774 + 0,505 PB + 0,344 BK + 0,283 MK. The equation indicates that readiness of work influenced by learning achievement of computer accounting subject, career guidance and work motivation. The conclusions are: 1) learning achievement of computer accounting subject, career guidance and work motivation partially significant effect on the work readiness of class XII students accounting skill program in SMK Negeri 1 Suboh Situbondo. 2). Learning achievement of computer accounting subject, career guidance and work motivation simultaneously have a significant effect on the work readiness of class XII students accounting skill program at SMK Negeri 1 Suboh Situbondo.